Pengaruh Gaya Hidup terhadap Penggunaan PayLater serta Dampaknya terhadap Kesejahteraan Mahasiswa di Yogyakarta - Roro Rahma Wijayanti; Yohanes Baptista Advent Rengu; Anita Tania Septianti (Jurnal Ilmu Sosial dan Humaniora, 2026)
The development of PayLater services among Yogyakarta students shows a significant upward trend in line with the emergence of a consumerist lifestyle and the influence of digital culture. Ease of access, attractive promotions, and social pressure through social media encourage students to use PayLater not only for their needs but also as a means of building self-image. This phenomenon raises concerns regarding financial responsibility and a decline in student well-being. This study aims to analyze the influence of lifestyle on PayLater usage and its impact on the well-being of students in Yogyakarta. Using a quantitative approach, this study tests three main hypotheses: the influence of lifestyle on PayLater usage, the influence of PayLater usage on well-being, and the role of PayLater usage as a mediator between lifestyle and well-being. The results are expected to provide a more comprehensive understanding of student consumer behavior in the digital era and its impact on their economic, social, and psychological conditions. These findings are expected to provide a basis for students, educational institutions, and digital financial institutions to improve financial literacy and encourage wiser use of digital credit services.